Neonatal segmental small bowel volvulus with normal intestinal rotation - Sravya Gourishetti; Stephen D. DeMeo (Elsevier, 2021)
Segmental small bowel volvulus is a condition in which a portion of bowel twists upon itself. The most common causes include malrotation and intestinal atresia. Volvulus can present at any age, but typically presents within the first few weeks of life. Presentation of midgut volvulus with normal mesenteric fixation and no malrotation is termed primary midgut volvulus. Unrecognized midgut volvulus leads to bowel ischemia and varying degrees of bowel necrosis. We present a rare case of Segmental small bowel volvulus without malrotation in a preterm neonate.On day of life 53, a preterm female born at 25 weeks gestation developed abdominal distention and respiratory distress. Abdominal x-ray showed distended, gas-filled loops of bowel and upper GI series showed no malrotation. Due to concerns for intestinal obstruction, an exploratory laparotomy was performed, which revealed a segmental small bowel volvulus with extensive necrosis, but no malrotation.A well-known complication of midgut volvulus is bowel ischemia, often leading to necrosis and sepsis. With the low prevalence of primary midgut volvulus, delayed diagnosis is common, which often leads to fatal outcomes. Therefore, primary midgut volvulus should be considered in all patients, including neonates that present with abdominal distention, shock, and signs of intestinal obstruction.